Synergistic Effect of Clinically Available Beta-Lactamase Inhibitors Combined with Cefiderocol against Carbapenemase-Producing Gram-Negative Organisms - Gabriele Bianco; Paolo Gaibani; Sara Comini; Matteo Boattini; Giuliana Banche; Cristina Costa; Rossana Cavallo; Patrice Nordmann (MDPI AG, 2022)
The role of β-lactamases in reduced susceptibility or resistance to cefiderocol has been supported by recent reports. The purpose of this study was to investigate the in vitro impact of clinically available β-lactamase inhibitors on cefiderocol activity against characterized carbapenemase-producing Gram-negative isolates. A collection of 39 well-characterized Gram-negative isolates obtained from various clinical sources and countries were included. Cefiderocol antimicrobial susceptibility was evaluated via reference broth microdilution. The chequerboard microdilution method and time-kill assays were used to determine the synergy of tazobactam, avibactam, vaborbactam and relebactam in combination with cefiderocol. MICs of cefiderocol presented a 4- to 256-fold reduction against Klebsiella pneumoniae carbapenemase (KPC)-producing Gram-negative isolates (predominantly K. pneumoniae) when avibactam, vaborbactam and relebactam were combined individually. Notably, the KPC-inhibitors led to a 4- to 32-fold reduction in cefiderocol MICs in the four cefiderocol-resistant KPC-producing K. pneumoniae isolates, showing restoration of cefiderocol susceptibility (MIC ≤ 2 mg/L) in ten out of twelve cases. Tazobactam led to a 4- to 64-fold decrease in cefiderocol MICs only in K. pneumoniae strains harbouring blaKPC-41, blaKPC-31, blaKPC-53 and blaKPC-66. The synergistic effect of all serine-β-lactamase inhibitors on cefiderocol activity was also shown in OXA-48-like-producing Enterobacterales strains. Conversely, a combination of β-lactamases inhibitors with cefiderocol was not synergistic with all OXA-23-like-producing strains and most metallo-β-lactamases producers. In conclusion, the addition of clinically available serine β-lactamase inhibitors to cefiderocol might represent an important development in the formulation to increase its spectrum and therapeutic efficacy, and to limit in vivo resistance emergence.